Effect of composite yeast culture on the jejunal barrier function, inflammatory response, and microbial community structure of laying hens during the late stage of egg production - Luo, Qifei; Yang, Lan; Tumenjargal, Bazarragchaa; Liu, Shixiong; Ma, Jiabin; Ning, Jie; Yun, Zichen; Zhang, Xiaojie; Wu, Yingga; Lu, Yu; Wu, Xiaoxuan; Wang, Lijuan; et al. (Frontiers in Veterinary Science, 2024)
During the late laying period, the intestinal barrier of laying hens is susceptible to damage, resulting in enteric infections and even systemic inflammatory responses, posing a major challenge for the poultry industry. Therefore, it is crucial to investigate methods for addressing intestinal inflammation in late laying hens. In order to maximize the production potential of egg laying chickens, farmers usually use various feed additives to prevent damage to the intestinal barrier. Composite yeast cultures have shown advantages in broiler applications. This study aims to assess the impact of composite yeast culture (CYC) on the intestinal barrier function, inflammatory cytokines, and microbial community structure of Hy-Line Brown laying hens. A total of 160 healthy Hy-Line Brown hens, aged 58 weeks and of similar weight, were randomly assigned to two groups, with four replicates per group and 20 hens in each replicate. The control group was fed a basal diet (Con), while the experimental group was provided with a diet supplemented with 40 g/kg of composite yeast culture (CYC). The test period was 25 days. The results indicated that: compared to the control group, CYC significantly improved the egg production rates of hens during days 11–15, 16–20, and 21–25 (p < 0.05). CYC significantly enhanced the relative mRNA expression levels of occludin, claudin-1, zonula occludens-1 (ZO-1), and mucin 2 (Muc2) in the intestinal tract (p < 0.05), while reducing the relative expression levels of pro-inflammatory factors TNF-α and IFN-γ (p < 0.05), and increasing the levels of anti-inflammatory factors IL-4, IL-10, and TGF-β1 (p < 0.05). CYC significantly increased the abundance of Bifidobacterium pseudocatenulatum and Faecalibacterium prausnitzii in the intestine. These findings suggest that the composite yeast culture (CYC) can improve the structure of the intestinal microbial community. In conclusion, CYC may enhance egg production rates, reduce inflammatory responses, and strengthen intestinal barrier function by modulating the composition of the intestinal microbiota in late laying hens.